PEMANFAATAN TEKNOLOGI ISNTAGRAM DALAM PROGRAM PEMBELAJARAN PAI: STRATEGI INOVATIF UNTUK PENGEMBANGAN KURIKULUM - Anisa Nurul Ikhsan; Fitriyani, Annisa; Asep Nursobah; Eri Hadiana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the Utilization of Instagram Technology in the PAI Learning Program: Innovative Strategies for Curriculum Development. The utilization of learning media technology with Instagram is designed to provide an innovation in PAI learning so that it can adapt to the current developments with the aim of having a major impact on the success of PAI learning in achieving the expected goals and also influencing curriculum development. With the library research method, namely the method of collecting data by understanding and studying theories from various literature or references. Data collection is carried out by searching for sources and constructing information from various sources, such as books, journals, and existing research. So that the journal on the utilization of Instagram technology in the PAI learning program: innovative strategies in curriculum development can be compiled.